2018
DOI: 10.1051/0004-6361/201731803
|View full text |Cite
|
Sign up to set email alerts
|

The envelope of the power spectra of over a thousand δ Scuti stars

Abstract: CoRoT and Kepler high-precision photometric data allowed the detection and characterization of the oscillation parameters in stars other than the Sun. Moreover, thanks to the scaling relations, it is possible to estimate masses and radii for thousands of solar-type oscillating stars. Recently, a Δν − ρ relation has been found for δ Scuti stars. Now, analysing several hundreds of this kind of stars observed with CoRoT and Kepler, we present an empiric relation between their frequency at maximum power of their o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…This is in agreement with the predicted frequency distribution for the κ-mechanism (Dziembowski 1977) since we detected higher frequency modes for higher temperature δ Scuti stars. In fact, our relation is similar to that found by Barceló Forteza et al (2018). We also observed that old stars with low surface gravity present lower frequency ranges (see Eq.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with the predicted frequency distribution for the κ-mechanism (Dziembowski 1977) since we detected higher frequency modes for higher temperature δ Scuti stars. In fact, our relation is similar to that found by Barceló Forteza et al (2018). We also observed that old stars with low surface gravity present lower frequency ranges (see Eq.…”
Section: Discussionsupporting
confidence: 91%
“…Using the large amount of stellar data from space missions like CoRoT (Baglin et al 2006) or Kepler (Borucki et al 2010), the scientific community has also been looking for scaling relations for δ Scuti stars (e.g. Suárez et al 2014;García Hernández et al 2015;Michel et al 2017;Moya et al 2017;Barceló Forteza et al 2018;Bowman & Kurtz 2018). In a contribution to extend ensemble asteroseismology, Barceló Forteza et al (2018, -BF18 hereafter-) describe the envelope of δ Scuti stars with several metrics such as the number of modes (N env ), the frequency at Tables A.1 and A.2 are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.…”
Section: Introductionmentioning
confidence: 99%
“…This is also consistent with findings that Kepler δ Sct stars with higher T eff tend to have shorter dominant periods, i.e. a higher ν max (Balona & Dziembowski 2011;Barceló Forteza et al 2018).…”
Section: Interpretation Of the P-l Diagramsupporting
confidence: 92%
“…Many δ Sct stars were observed by Kepler during its fouryear nominal mission (e.g., Balona & Dziembowski 2011;Balona et al 2015;Bradley et al 2015;Moya et al 2017;Balona 2018;Barceló Forteza et al 2018;Bowman & Kurtz 2018). We have used the sample of about 2000 δ Sct stars identified by Murphy et al (2019) from Kepler long-cadence data.…”
Section: Kepler δ Sct Starsmentioning
confidence: 99%
“…An unexpected discovery was that many pulsating A and F stars are hybrid pulsators exhibiting both p and g modes (Grigahcène et al 2010;Balona & Dziembowski 2011;Uytterhoeven et al 2011), although pure pulsators of both types do exist (see e.g. Van Reeth et al 2015a;Bowman 2017;Barceló Forteza, Roca Cortés & García 2018;Li et al 2019a). The high incidence of hybrid stars remains unexplained, particularly if a single excitation mechanism should be responsible for both the p and g modes in hybrid stars (Balona, Daszyńska-Daszkiewicz & Pamyatnykh 2015;Xiong et al 2016).…”
mentioning
confidence: 99%